Early experience with a multi-axial, whole body positioning system in the treatment of Benign Paroxysmal Positional Vertigo (BPPV). (March 2019) - Power, L.; Murray, K.; Szmulewicz, D.
Highlights: BPPV was identified in 79 out of 216 patients. Thirty-five (44%) experienced resolution after one manoeuvre, and 74 (94%) after three manoeuvres. Bilateral posterior, multiple canal and cupulolithasis were most likely to be treatment refractory. A whole body positioning system is a valuable tool in the diagnosis and management of BPPV.